CALCULATION METHODS OF OPTIMAL ADJUSTMENT OF CONTROL SYSTEM THROUGH DISTURBANCE CHANNEL - I. M. Golinko; G. G. Kulakov; Yu. M. Kovrigo (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
In the process of automatic control system debugging the great attention is paid to determining formulas’ parameters of optimal dynamic adjustment of regulators, taking into account the dynamics of Objects control. In most cases the known formulas are oriented on design of automatic control system through channel “input-output definition”. But practically in all continuous processes the main task of all regulators is stabilization of output parameters. The Methods of parameters calculation for dynamic adjustment of regulations were developed. These methods allow to optimize the analog and digital regulators, taking into account minimization of regulated influences. There were suggested to use the fact of detuning and maximum value of regulated influence. As the automatic control system optimization with proportional plus reset controllers on disturbance channel is an unimodal task, the main algorithm of optimization is realized by Hooke – Jeeves method. For controllers optimization through channel external disturbance there were obtained functional dependences of parameters calculations of dynamic proportional plus reset controllers from dynamic characteristics of Object control. The obtained dependences allow to improve the work of controllers (regulators) of automatic control on external disturbance channel and so it allows to improve the quality of regulation of transient processes. Calculation formulas provide high accuracy and convenience in usage. In suggested method there are no nomographs and this fact expels subjectivity of investigation in determination of parameters of dynamic adjustment of proportional plus reset controllers. Functional dependences can be used for calculation of adjustment of PR controllers in a great range of change of dynamic characteristics of Objects control.